Kinetic Analysis of Consecutive First Order Reaction: Oxidation of Malonic Acid Dihydrazide - Hogale, M.B.; Pawar, P.K. (Asian Journal of Chemistry, 2010)
The kinetic analysis of oxidation of malonic acid dihydrazlde in mild alkaline medium by hexacyanoferrate (III) have been studied. The analysis suggests that the oxidation of studied dihydrazide follows conscecutive first order irreversible path. The oxidation products of preceding and slow step of reaction were complex of enolate of dihydrazide with hexacyanoferrate (III), malonic acid monohydrazide and nitrogen respectively. The rate constants k2 and k3 for second and third steps of the reaction calculated by Swain´s method were found to be identical with those calculated by Powell´s graphical method. The reaction is studied at various temperatures to evaluate the activation parameters.